2021
DOI: 10.15252/embr.202052006
|View full text |Cite
|
Sign up to set email alerts
|

MICAL2PV suppresses the formation of tunneling nanotubes and modulates mitochondrial trafficking

Abstract: Tunneling nanotubes (TNTs) are actin-rich structures that connect two or more cells and mediate cargo exchange between spatially separated cells. TNTs transport signaling molecules, vesicles, organelles, and even pathogens. However, the molecular mechanisms regulating TNT formation remain unclear and little is known about the endogenous mechanisms suppressing TNT formation in lung cancer cells. Here, we report that MICAL2PV, a splicing isoform of the neuronal guidance gene MICAL2, is a novel TNT regulator that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 99 publications
(162 reference statements)
2
24
0
Order By: Relevance
“…Immunofluorescence staining was performed following our published protocol 41 using a polyclonal rabbit anti-PGS1(Sigma-Aldrich, Cat# AV48896) and secondary antibody conjugated with Alexa-488 (Abcam, Cat# ab150081).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence staining was performed following our published protocol 41 using a polyclonal rabbit anti-PGS1(Sigma-Aldrich, Cat# AV48896) and secondary antibody conjugated with Alexa-488 (Abcam, Cat# ab150081).…”
Section: Methodsmentioning
confidence: 99%
“…The control shRNA construct (shCtr) was as previously described 41 . A shPGS1 construct was designed to express shRNA against PGS1 (target sequence: 5'-TCGGGTTCCATCCGTTTAAAT-3') in the plasmid vector Tet-pLKO-puro (Vector Builder Inc) to specifically down-regulate expression of PGS1following induction with tetracycline (Tet).…”
Section: Sample Preparation Hek293 Cell Culturesmentioning
confidence: 99%
“…Miro proteins provide tethering of mitochondria to cytoskeletal motor proteins and serve as regulators of transport of the organelles, based on their calcium-dependent activity (Eberhardt et al, 2020;Nahacka et al, 2021). Essential role of Miro in intercellular transfer of mitochondria has been demonstrated by many studies reporting a correlation between Miro expression and mitochondria exchange with TNTs being the conduits for the transport (Ahmad et al, 2014;Babenko et al, 2018;English et al, 2020;Tseng et al, 2021;Wang et al, 2021). Except for one study, presence of Miro was found essential for the transfer/movement of mitochondria along TNTs rather than for their formation (Babenko et al, 2018;Raghavan et al, 2021).…”
Section: Mechanism Of Mitochondrial Transfer Via Tnts and The Role Of...mentioning
confidence: 99%
“…Additionally Miro1 and partially Miro2 have been shown to be important for mitochondrial transport towards the cell periphery, especially in case of energy-demanding processes such as migration and invasion of cancer cells ( Caino et al, 2016 ; Lopez-Domenech et al, 2018 ; Wang et al, 2021 ). Knock-out of these two proteins results in perinuclear localization of mitochondria, with more prominent phenotype in case of Miro1/Miro2 double knock-out ( Kittler, 2015 ).…”
Section: Tunneling Nanotubesmentioning
confidence: 99%
“…A recent study has shown that the monooxygenase domain of MICAL2PV, a spliced isoform product of the neuronal guidance gene MICAL2, interacts with Miro-2, inhibiting TNT formation by depolymerization of f-actin. MICAL2PV plays crucial role in cell survival and down-regulation of MICAL2PV, and protect lung cancer cells treated with chemotherapeutic drugs [ 123 ].…”
Section: Rho Gtpase Related Signals Counteract Apoptosis Via Tunnelling Nanotubesmentioning
confidence: 99%